Pengaruh Penggunaan Media Pembelajaran Audio Visual Terhadap Minat Belajar Siswa Pada materi Sistem Pernafasan Kelas V SD - Cahyani, Ita Dwi; Afifah, Uci Ulfa Nur; Utami, Novia Rahma Rista (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2024)
The purpose of this study was to determine the effect of the use of audio-visual learning media on students' learning interest about the respiratory system in class V. The method used was quantitative with a pre-test and post-test group design. The population of this study was all students of SDN Banjarbanggi 1 and the samples were taken using purposive sampling techniques, namely grade V students of SDN Banjarbanggi 1 totaling 15 people. Data was collected using questionnaires and data analysis was carried out through testing questionnaire instruments in the form of validity and reliability tests, prerequisite tests in the form of normality and homogeneity tests, and hypothesis tests using paired sample t-tests. The results showed that the use of audio-visual learning media was effective and students' interest in learning increased after treatment with these media. The use of audio-visual learning media has a significant influence on student interest in respiratory system learning materials in class V.